STUDENTS' SPEAKING ANXIETY IN EFL CLASSROOMS - RAMDHANI, Deni (2012)
This study was designed to investigate speaking anxiety among English students of a vocational school. A total of 23 students of a vocational high school in Bandung participated in the study. This qualitative study investigated the levels of students' speaking anxiety, the sources of their speaking anxiety, and the strategies they employed in coping with the anxiety encountered. To collect the data, an adapted Foreign Language Classroom Anxiety Scale (composed by Horwitz, et al., 1986) and interviews were employed. The study found majority of the students were at moderate level of anxiety (52,2%). In addition, six students fell in low anxiety level (26,1%) and five other students were at high anxiety level (21,7%). The sources of the students' speaking anxiety derived from: personal and interpersonal anxiety, student's beliefs about English learning, teacher-student interactions, classroom activities and language testing. The study also found most participants applied the relaxation strategy among the five strategies proposed by Kondo (2004), i.e. preparation, relaxation, positive thinking, peer seeking, and resignation. These findings suggest that it is vital to control the level of anxiety as it affects students' performance. Therefore, future research needs to seek more practical solutions in reducing student speaking anxiety in order to help the students in achieving their goal in learning English.